The development of socially responsible marketing in international business - Stelmashuk, Kamila Oleksiyivna (Волинський національний університет імені Лесі Українки, 2025)
The relevance of the topic is driven by the growing importance of socially responsible marketing in today’s globalized world, which faces social, environmental, and ethical challenges. Particular attention is paid to the role of socially responsible marketing in international business and its adaptation in the Ukrainian context amid war and European integration. The bachelor’s thesis explores the theoretical and methodological foundations, current practices, and development prospects of socially responsible marketing. The first chapter reveals the essence of socially responsible marketing, its principles, functions, and role in international business, as well as the influence of global initiatives on its development. The second chapter analyzes current trends and challenges in the field of socially responsible marketing, examines examples of its implementation by leading international companies, and identifies threats to its development in conditions of global instability. The third chapter characterizes the state and prospects of socially responsible marketing development in Ukraine, particularly in the context of war, socio-economic crisis, and European integration, and outlines opportunities for Ukrainian businesses.
Keywords: socially responsible marketing; international business; sustainable development; corporate social responsibility; Ukraine; European integration